2007
DOI: 10.1016/j.physbeh.2007.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Running is rewarding and antidepressive

Abstract: Natural behaviors such as eating, drinking, reproduction and exercise activate brain reward pathways and consequently the individual engages in these behaviors to receive the reward. However, drugs of abuse are even more potent to activate the reward pathways. Rewarding behaviors and addictive drugs also affect other parts of the brain not directly involved in the mediation of reward. For instance, running increases neurogenesis in hippocampus and is beneficial as an antidepressant in a genetic animal model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 52 publications
4
123
1
1
Order By: Relevance
“…The 78% increase in the individual performance of the rewarded runners during the second week of the experiment shows that an ordinary C57Bl/6 mouse performs at no more than ~60% of its maximum potential. Several studies in C57Bl/6 mice have interpreted a continuous increase of performance during the experimental period as an addiction effect, which was also supported by the finding that the mesolimbic dopaminergic system reacts similarly to that seen after drug intake [21,[47][48][49]. In our study we observed a 7% increase of running performance within the non-rewarded running group which is much less than reported previously.…”
Section: Running For a Rewardsupporting
confidence: 85%
See 1 more Smart Citation
“…The 78% increase in the individual performance of the rewarded runners during the second week of the experiment shows that an ordinary C57Bl/6 mouse performs at no more than ~60% of its maximum potential. Several studies in C57Bl/6 mice have interpreted a continuous increase of performance during the experimental period as an addiction effect, which was also supported by the finding that the mesolimbic dopaminergic system reacts similarly to that seen after drug intake [21,[47][48][49]. In our study we observed a 7% increase of running performance within the non-rewarded running group which is much less than reported previously.…”
Section: Running For a Rewardsupporting
confidence: 85%
“…Exceeding a threshold is required to find neurogenesis rates significantly different from control animals [16]. In addition, running improves cognitive [17] and spatial learning abilities [13,14], has antidepressant [18] and anxiolytic effects [19,20] and positively stimulates the reward pathways in a way similar to drug abuse [21]. Chronic anxiolytic treatment with antidepressant drugs has been shown to increase neurogenesis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting contradiction exists in this respect regarding the direction of the generally positive effect of exercise on AN. Exercise is generally associated with beneficial changes, also in its effects on mood (Ernst et al 2006;Brené et al 2007;Kannangara et al 2011;Vivar et al 2013) and known to potently increase neurogenesis. Paradoxically, GCs are also increased during running.…”
Section: Stress Regulates Adult Hippocampal Neurogenesismentioning
confidence: 99%
“…The deleterious effect of many negative regulators of AHN, including ageing [50], stress/depression (reviewed in [10]) and pregnancy [95], can be offset by running or providing an enriched environment in rodents. However, the molecular mechanisms by which physiological and environmental changes influence AHN remain to be fully understood.…”
Section: Environmental Modulation Of Adult Hippocampal Neurogenesismentioning
confidence: 99%